2016
DOI: 10.1111/ppl.12422
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific variation in localization of hypericins and phloroglucinols in the genus Hypericum as revealed by desorption electrospray ionization mass spectrometry imaging

Abstract: Plants of the genus Hypericum are widely known for their therapeutic properties. The most biologically active compounds of this genus are naphtodianthrones and phloroglucinols. Indirect desorption electrospray ionization mass spectrometry (DESI-MS) imaging allows visualization and localization of secondary metabolites in different plant tissues. This study is focused on localization of major secondary compounds in the leaves of 17 different in vitro cultured Hypericum species classified in 11 sections. General… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 31 publications
8
20
0
Order By: Relevance
“…Our results are in agreement with the work of Soelberg et al (2007) who used UV-HPLC to detect hyperforin in the translucent glands as well as in minute amounts in dark glands of H. perforatum . In our present study, hyperforin was found to be absent in H. maculatum, H. erectum , and H. tetrapterum , which is in accordance with our earlier study (Kucharíková et al, 2016). This further demonstrates that the accumulation pattern of selected phytochemicals in these in vitro cultured Hypericum spp.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our results are in agreement with the work of Soelberg et al (2007) who used UV-HPLC to detect hyperforin in the translucent glands as well as in minute amounts in dark glands of H. perforatum . In our present study, hyperforin was found to be absent in H. maculatum, H. erectum , and H. tetrapterum , which is in accordance with our earlier study (Kucharíková et al, 2016). This further demonstrates that the accumulation pattern of selected phytochemicals in these in vitro cultured Hypericum spp.…”
Section: Discussionsupporting
confidence: 93%
“…Their results confirm the localization of hypericin in the dark glands of leaves and petals, and pseudohypericin and protohypericin in the dark glands of leaves of H. perforatum . More recently, we confirmed the localization and/or co-localization of hypericin, pseudohypericin and their protoforms in the dark glands of leaves of the four aforementioned in vitro cultured species belonging to the section Hypericum using indirect DESI-MSI (Kucharíková et al, 2016). …”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations